PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PEMAHAMAN ILMU TAJWID SISWA MELALUI METODE READING GUIDE - Muhammad Romi; Nia Wardhani; Yusnaini (Program Studi Manajemen Pendidikan Islam, 2022)
The role of Islamic Education (PAI) teachers is very strategic in improving students' understanding of tajwid. At SMP Ihdal Ulum Al Aziziah, Samalanga Sub-district, Bireuen District, the Reading Guide method is employed to guide students in reading the Quran correctly according to tajwid rules. This study adopts a qualitative case study approach, with data collection techniques including interviews, observations, and documentation. The results indicate that the Reading Guide method effectively enhances students' focus and active participation, particularly in the pronunciation of Arabic letters according to their proper articulation points (makhrajul huruf). This method facilitates students in imitating the teacher's recitation (musyafahah bil ada’), which plays a crucial role in developing fluency in reciting the Quran. Continuous practice and individual reinforcement are also necessary to avoid stiffness in pronunciation. Teacher professionalism, learning environment support, and facility availability also determine the success of this method. However, obstacles were also found, such as the lack of readiness of students who were slow to understand or lacked confidence, as well as the need for teachers to prepare interesting teaching materials. With the right approach, this method can be an effective strategy in tajwid learning